2019
DOI: 10.3389/fneur.2019.00574
|View full text |Cite
|
Sign up to set email alerts
|

The Gut and Parkinson's Disease—A Bidirectional Pathway

Abstract: Humans evolved a symbiotic relationship with their gut microbiome, a complex microbial community composed of bacteria, archaea, protists, and viruses, including bacteriophages. The enteric nervous system (ENS) is a gateway for the bidirectional communication between the brain and the gut, mostly through the vagus nerve (VN). Environmental exposure plays a pivotal role in both the composition and functionality of the gut microbiome and may contribute to susceptibility to neurodegenerative disorders, such as Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 139 publications
0
86
0
5
Order By: Relevance
“…Lewy bodies are present not only in the central nervous system (CNS) but also in the enteric nervous system (ENS) of the intestine, so it is not only the brain but also the gut that is involved in PD pathogenesis 10,11 . In 2002, Del Tredici et al postulated that neurotoxic α-synucleins may originate in the gut and migrate to the brain via the vagal nerve, the gutbrain-axis, causing neuronal cell death and inflammation in the substantia nigra 12,13,14,15,16 . This theory was recently supported by studies in rat models 17,18,19 , which confirmed that α-synuclein transport can be purged by vagal nerve resection 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Lewy bodies are present not only in the central nervous system (CNS) but also in the enteric nervous system (ENS) of the intestine, so it is not only the brain but also the gut that is involved in PD pathogenesis 10,11 . In 2002, Del Tredici et al postulated that neurotoxic α-synucleins may originate in the gut and migrate to the brain via the vagal nerve, the gutbrain-axis, causing neuronal cell death and inflammation in the substantia nigra 12,13,14,15,16 . This theory was recently supported by studies in rat models 17,18,19 , which confirmed that α-synuclein transport can be purged by vagal nerve resection 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson's disease (PD) is a common neurodegenerative disorder associated with the progressive loss of dopaminergic neurons located in the midbrain nucleus substantia nigra pars compacta (SNpc) due to the accumulation of αsynuclein (α-syn) aggregates. The Braak hypothesis (9) for the etiology of sporadic Parkinson's disease (PD) proposes that a neurotropic virus invading neural tissue through the nasal cavity and the gastrointestinal tract causes α-syn to turn into a promiscuous binder and be transmitted, prion-like, to key areas such as the SNpc (15). Interestingly, the prodromal or preclinical phase of PD is also characterized by olfactory and gastrointestinal symptoms (17).…”
mentioning
confidence: 99%
“…Recent discoveries in the field of the gut microbiome and their role in the neurodegeneration in patients and animal models highlights an important link among each other (67). As most of the common neurodegenerative diseases such as Alzheimer's disease and PD occurs late in the life (40,68) biomarkers allowing early diagnosis would be invaluable.…”
Section: Discussionmentioning
confidence: 99%
“…Immune cells are capable of engaging in direct communication with enteric neurons (18,20). The extent of the functional impact of neuro-immune synapses is not clear yet however published studies advocated that activated immune cells can temper neuronal activity via the release of neurotransmitters, metabolites and cytokines (19,39,40). Based on the common occurrence of GIT symptoms in PD, dysbiosis among PD patients, and evidence that the microbiota impacts CNS function, we hypothesized that DJ-1 protein could also be involved in the regulation of the gut microbiome and inflammation.…”
Section: Introductionmentioning
confidence: 99%